PENGEMBANGAN INSTRUMEN WIDAâS UNTUK MENGUKUR KINERJA PERAWAT PELAKSANA - Widaningsih, Widaningsih; Nurachmah, Elly; Waluyo, Agung; Mansyur4, Muchtarudin (Indonesian Journal of Nursing Health Science, 2016)
Abstract The development of performance measurement instruments nurse is required to identify the performance of nurses in the care of patients, especially in intensive care . This study uses Wida instruments that focus on the level of performance -based nurse nursing process and characteristics of such as gender , age , years of service, the amount of training , the workplace and educational backgrounds . The samples were nurses who work in hospital intensive care class A and B in Indonesia ( 722 respondents ) . The results using Wida instrument can measure the performance of nurses in intensive care , although there is the influence of the characteristics of nurses such as age, sex , duration of work , educational background , and the amount of training . Obtaining the results of these studies have implications in the management of the performance of nurses in intensive care were supported by the Hospital management policies. Keywords: nurseâs characteristics, intensive care, widaâs instrument